Rancang Bangun Aplikasi Patroli Security/Satpam Berteknologi NFC (Near Field Communication) dan Google Maps API sebagai Service Data Spasial berbasis Android - Ovriawan Aldo Pribadi Putra; Barlian Henryranu Prasetio; Aryo Pinandito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The recovery of living conditions after the pandemic has forced the community to start designing and reorganizing their business, be it a business in the form of a product or a service. Nevertheless, the security of business or business assets must remain a top priority. So in practice, professional security services are needed with the latest technology to minimize unwanted things while on duty/patrolling in the security area. Now conventional methods are slowly being replaced by digital patrolling innovations. Astha Slur: Security Labor Utility Remote is a digital security patrol application with NFC (Near Field Communication) technology and Google Maps API as an Android-based spatial data service. NFC itself is a radio frequency communication technology that can read addresses on tags as a reader. At the same time, the Google Maps API is a technology that is used for mapping in security areas. Both of these technologies can record situations and conditions in real-time and applications embedded with the Android OS can be easily operated by all security personnel.